Depositional environment of the Bagh-e-Vang Formation – the only occurrence of upper Lower Permian in Iran - Yegane, Bizhan Yousefi; van Loon Tom, A.J.; Fard, Sakine Arefi; Farahpour, Mohammad Mehdi; Sharahi, Safoora Yasbolaghi (Geologos, 2021)
A transgression of the Tethys Ocean occurred in east central Iran, like in other areas of the Tethys Ocean, around the Yakhtashian/Bolorian (regional chronostratigraphical units corresponding with the Artinskian/Kungurian of the Early Permian) transition. This led to the development of a carbonate platform that is represented in the Shirgesht area on the northern part of the Tabas Block by the Bagh-e-Vang Formation, which constitutes the only known sedimentary unit from the late Early Permian in Iran. Field data and thin-section analysis indicate deposition on a carbonate ramp with barriers separating a lagoonal area with intertidal mud flats from the open-marine environment. The overall transgressive development is indicated by the presence of open-marine sediments on top of the barrier and lagoonal sediments.